From 'back' to 'again' in Dutch: The structure of the 're' domain. (16th November 2018) - Zwarts, Joost
Abstract: On the basis of a model-theoretic analysis of the polysemy of the Dutch adverb terug (covering 'back' and 'again') and its partial synonyms, a semantic map is constructed that (i) explains how backward direction in space relates to repetition in time and what role counterdirectionality plays in that relation, (ii) integrates, in a semantically motivated way, various meanings that have been identified in separate strands of research, and (iii) allows polysemous items living in this domain to have a coherent semantic basis.